Prevalence of urinary tract infection and sensitivity pattern in febrile children less than 5 years of age - Gupta, Manoj Kumar; Yadav, Dhirendra Prasad; Ansari, M. Ashfaque (International Journal of Contemporary Pediatrics, 2022)
Background: Fever has long been considered as an important clinical finding in children with urinary tract infections (UTIs), it is often ignored in children in whom the symptoms are fuzzy. UTI in children is alarming because of the acute and chronic complications not seen routinely in adults. The study emphasizes that UTI should be strongly suspected in febrile children to prevent future complications. This study was undertaken to determine the prevalence of UTI and sensitivity pattern in febrile children and to assess the validity of microscopic urine analysis against urine culture in the diagnosis of UTI. Methods: A descriptive study was undertaken in the department of pediatrics, NMCTH, Birgunj. Data related to age, sex, nutritional status, socioeconomic status were noted. Physical examinations with relevant investigations were carried out in all those patients. Results: Out of 1074 children 147 showed significant pyuria (13.7%) and 44 showed significant bacterial growth making an overall prevalence of 4.1%. Urine cultures were done in all the cases and showed positive culture in 29.93%. Among culture positive cases gram negative organisms were commonly isolated. E. coli (70.45%) commonly isolated in the culture was found highly sensitive to cefotaxime and sulphamethoxazole /trimethoprim (32.14%) and was highly resistance to cefepime, cefuroxime, cefixime. Conclusions: Overall prevalence of UTI in our study was low (4.1%). The >5 pus cells/hpf in centrifuged sample should be considered as significant pyuria and further evaluation should be done promptly to initiate treatment and to prevent long term sequalae.